PENGARUH MEDIA CELEMEK CERITA TERHADAP KEMAMPUAN MENYIMAK ANAK USIA DINI KELOMPOK B TK BUNDA RINNY SARTIKA - Innaya Tantry Surya; Aminda Tri Handayani (STKIP Subang, 2024)
This research aims to (1) the listening skills of young children in storytelling activities; (2) children are able to respond and communicate well through stories told by researchers; (3) see whether or not the story apron media has an influence on children's listening abilities. The design of this research method uses a one group pretest-posttest design research model, that in this type of method there is a pretest before the treatment is carried out. In this way, the results of the treatment can be known more accurately because they can be compared with the initial conditions before the treatment was carried out. The sample in this study was 30 class B children, but 15 people were the subjects and the child population was 40 people. The method used for collecting research data is through observation. The method for analyzing research data is the t-test. As a result of this research, the researcher concluded that there was an influence of learning using story apron media on the listening ability of group B children at Bunda Rinny Sartika Kindergarten 2024. It can be proven from the results of hypothesis calculations carried out during the posttest and the results of the data normality test. It can be seen that the variants are declared homogeneous. then when testing the hypothesis from the results of the t-test calculations, the value obtained or t_count>t_tabel or 3.43> 1.782 which can be interpreted as accepting〖H〗_and rejecting H_(0,) and from the results of this research hypothesis it states that there is a significant influence with the use story apron media on children's listening skills.